1972
DOI: 10.1111/j.1365-2362.1972.tb00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activity in Human Skeletal Muscle Effect of Peripheral Arterial Insufficiency

Abstract: Succinic oxidase activity and the incorporation rates of glucose-carbon into glycogen, lipids, lactate and carbon-dioxide were studied in vitro in samples of skeletal muscle taken from patients with peripheral arterial insufficiency.In the patients with intermittent claudication significantly increased succinic oridase activity and incorporation rates of glucose-carbon were found in muscle tissue taken from the medial head of the gastrocnemius muscle. In patients with evidence of ischaemia a t rest the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…which has a higher proportion of glycolytic fibres which are not adapted to long-lasting contractions. Activity of oxidative enzymes has previously been shown to increase in muscles with decreased blood supply (Holm, Bjorntorp & Schersten, 1972) and in some cases of high-altitude hypoxia (Valdivia, 1958), where capillary growth has been described (Valdivia, 1958;Eby & Banchero, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…which has a higher proportion of glycolytic fibres which are not adapted to long-lasting contractions. Activity of oxidative enzymes has previously been shown to increase in muscles with decreased blood supply (Holm, Bjorntorp & Schersten, 1972) and in some cases of high-altitude hypoxia (Valdivia, 1958), where capillary growth has been described (Valdivia, 1958;Eby & Banchero, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for underlying muscle damage and degeneration in ambulatory IC patients has been presented [15,16] but such observations may reflect co-morbidities and have not been directly linked to IC symptoms. In the studies by Holm et al [13] muscle tissue from IC patients demonstrated an increased mitochondrial enzyme capacity. In patients with resting ischemia (and loss of mobility) this increased enzymatic activity was no longer observed [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the observations of Holm et al [10] and Schersten et al [35] concerning the metabolic activity of the skele tal muscles in patients with peripheral arterial insufficiency are also very suggestive. It is known that, under a hypoxic condition, physiological hy drogen acceptors other than oxygen and, especially, nicotinamide adenine nucleotides (NAD+ and NADP+) are temporarily involved to a greater ex tent in the tissular reduction-oxidation processes [32], It is also known that three molecules of ATP are enzymatically dephosphorylated for each molecule of NAD+ which is reduced, and, conversely, an equal number of ATP molecules are synthetized (by activity reversal of an ATPase) for each molecule of reduced NAD+ (NADH) which is oxidized by way of cell respiratory chain [36].…”
Section: Discussionmentioning
confidence: 71%